Faster breaststroke
Author asks: How can you improve fastest in your breaststroke races? Some facts: Breaststrokers are usually more heavily muscled than swimmers of the other strokes. Additional muscles size leads to more resistance from the water. Breaststroke is swum more in and under the water, this causes more resistance. This makes you slow down faster than the other strokes. Researchers have proven that Breaststroke takes more strength and more energy (calories) than the other strokes (yes even butterfly)! When velocity increases, the resistance increases by the square of the speed. Energy used increases by the cube of the speed. Thus, you must never try to overcome the resistance that you create by going faster. You must focus on eliminating resistance, not overcoming it. Therefore, improving your streamlining and reducing areas that slow you down are very important for Breaststrokers. Author shows the easiest ways to eliminate resistance.